The impact of transcranial direct current stimulation on the neuro-muscular control strategies of penalty kicks in soccer players - Wang, Haoyang; Zhang, Hongxiang; Li, Xin; Zhu, Jinbang (Frontiers in Sports and Active Living, 2025)
ObjectiveThis study aims to investigate the effects of transcranial direct current stimulation (tDCS) on the neuromuscular control of penalty kicks in soccer players. It also analyzes the relationship between neuromuscular control and the stability of motor performance following the intervention.MethodsWireless surface electromyography (EMG) data were synchronously collected from 20 national first-level athletes during penalty kicks using a wireless EMG acquisition device. To obtain spinal-level motor output, the EMG signal envelopes were inversely mapped to the α-motor neuron pools across various spinal segments. Muscle synergy characteristics were analyzed using non-negative matrix factorization and K-Means clustering.ResultsDuring the stance foot contact phase, tDCS led to more concentrated and less variable activation of lower limb muscle synergy, enhancing control of support and force transfer. In the kicking leg swing phase, muscle synergy was activated earlier and decayed more rapidly, maintaining swing velocity and ball striking accuracy while reducing energy expenditure. Additionally, anticipatory synergy adjustments appeared before movement transitions, indicating improved anticipatory action and adjustment capabilities after the intervention. As a result, neuromuscular control optimized the spatiotemporal structure of synergy, improving coordination and yielding more stable penalty kick performance.ConclusionTranscranial direct current stimulation can enhance neuromuscular control efficiency by optimizing spinal motor output and improving the spatiotemporal structure of muscle synergy. This results in more stable and effective kicking actions. Reasonably adjusting the timing of tDCS intervention can help improve soccer players’ kicking performance.